Effectiveness of a calcium silicate hydrate – Polycarboxylate ether (C-S-H–PCE) nanocomposite on early strength development of fly ash cement. (30th April 2018) - Kanchanason, V.; Plank, J.
Graphical abstract: Highlights: Synthetic C-S-H–PCE nanocomposite prepared by co-precipitation from Na2 SiO3 /Ca(NO3 )2 . C-S-H–PCE enhances early strength (6–24 h) of mortar and concrete of fly ash cement. No any adverse effect on final strength. C-S-H–PCE accelerates silicate hydration C-S-H–PCE also stimulates the pozzolanic reaction of fly ash. Abstract: C-S-H–PCE nanocomposites are known seeding materials for Portland cement. Here, the effectiveness of a C-S-H–PCE admixture on early strength development of a fly ash blended cement (35 wt% fly ash) was investigated. It was found that addition of C-S-H–PCE drastically increases the compressive strength of mortar and concrete, particularly at 6–24 h of hydration. XRD and calorimetric measurements confirm that the hydration of C3 S/C2 S in cement is greatly accelerated. Most interestingly, however, the C-S-H–PCE nanocomposite also stimulates the pozzolanic reaction of fly ash, thus explaining the exceptionally high early strength values. Accordingly, C-S-H–PCE might also be useful in other CEM II cements holding pozzolanic materials.